Comfort from suicidal cognition in recurrently depressed patients. - Crane, C; Barnhofer, T; Duggan, D; Eames, C; Hepburn, S; Shah, D; Williams, J (2014)
BACKGROUND: Previous research has suggested that some individuals may obtain comfort from their suicidal cognitions. METHOD: This study explored clinical variables associated with comfort from suicidal cognition using a newly developed 5 item measure in 217 patients with a history of recurrent depression and suicidality, of whom 98 were followed up to at least one relapse to depression and reported data on suicidal ideation during the follow-up phase. RESULTS: Results indicated that a minority of patients, around 15%, reported experiencing comfort from suicidal cognitions and that comfort was associated with several markers of a more severe clinical profile including both worst ever prior suicidal ideation and worst suicidal ideation over a 12 month follow-up period. LIMITATIONS: Few patients self-harmed during the follow-up period preventing an examination of associations between comfort and repetition of self-harm. CONCLUSIONS: These results, although preliminary, suggest that future theoretical and clinical research would benefit from further consideration of the concept of comfort from suicidal thinking.